Analisis Kebijakan Pemberian Penghargaan dan Pengenaan Sanksi Atas Pelaksanaan Anggaran Pendapatan dan Belanja Daerah - Lestari, Shinta Tri; Hutagaol, Henry Darmawan (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The administration of regional government is part of the administration of the NKRI government which mutually forms authority and financial relations between them. The enactment of Law Number 1 of 2022 perfects the pattern of central and regional financial relations and increases control from the central government over the implementation of the APBD through reward and punishment. The problem is how the policy of awarding and punishment is based on Law Number 1 of 2022 and efforts to improve it. Through normative juridical research methods and by making comparisons with China, it can be concluded that the policy of awarding and sanctioning is a form of responsibility of the central government as the giver of authority along with the allocation of funds as well as supervisors to ensure improvement and/or achievement of local government performance in terms of regional financial management , government public services and basic services. Efforts to improve it are carried out by improving financial governance in accordance with the concept of performance-based budgeting, paying attention to the placement of staff, the budgeting process through community participation, timely determination of technical guidelines and implementation instructions for budget disbursement, as well as correction of the APBD through central supervision which directly supervises regional development. Looking at the policies in China, there is an expansion in the form of awards that are given not only as incentives in the form of additional money but also by giving more authority to the regions.